Sosialisasi Menggunakan Haksuara Dan Don't Abstain Pada Pemilu 2024 Untuk Generasi Muda Di Desa Bongohulawa - Melo, Ramla Hartini; S. Niode, Alim; Lasulika, Cindy; Zakaria, Muhammad Rejki (-, 2024)
People who do not exercise their right to vote while voting are called abstainers. When it comes to the 2024 elections, the company needs to understand the negative consequences of not participating and develop countermeasures. In Indonesia, the process of strengthening political awareness and government actions to preserve Pancasila and the 1945 Constitution is known as "military training for youth". ". Their main characteristics are their strong sense of duty and their desire to pass on their traditions to future generations. In this context, the access and information needed to participate in the elections are of great importance. This research uses educational, participatory, observational and campaign methods to help people understand how to be honest and trustworthy. MBKM will be held in Bongohulawa Village between January 16 and February 20, 2024. During implementation, this event will be controlled by the MBKM Planning Committee and the local government with strict and strict supervision. This study aims to increase political awareness and participation in society through various social and educational activities.